2021
DOI: 10.1126/science.abc7303
|View full text |Cite
|
Sign up to set email alerts
|

Antibody fucosylation predicts disease severity in secondary dengue infection

Abstract: Although antiviral antibodies generally confer protective functions, antibodies against dengue virus (DENV) are associated with enhanced disease susceptibility. Antibodies can mediate DENV infection of leukocytes via Fcγ receptors, likely contributing to dengue disease pathogenesis. To determine if this mechanism accounts for variable disease severity, we examined Fab and Fc structures of anti-DENV antibodies from patients before and after infection and with variable disease outcomes. Neither antibody titers n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 32 publications
(10 reference statements)
6
77
0
Order By: Relevance
“…Furthermore, post-translational modifications of IgG antibodies have been shown to significant impact their affinity for FcgR complexes and to correlate with dengue severity (41). Most notably, the presence of high levels of afucosylated IgG-a posttranslational modification which increases the affinity of the IgG Fc domain for FcgRIIIa (42)either before or after DENV infection has been associated with increased dengue severity (43)(44)(45). Finally, the presence of serum complementsuch as C1q and C3 -can inhibit IgG mediated ADE both in vitro and in vivo, ostensibly by interfering with the ability of IgG Fc to interact with FcgR and/or forcing a complement-bound antibody into a configuration that is not amenable to fusion and viral entry (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, post-translational modifications of IgG antibodies have been shown to significant impact their affinity for FcgR complexes and to correlate with dengue severity (41). Most notably, the presence of high levels of afucosylated IgG-a posttranslational modification which increases the affinity of the IgG Fc domain for FcgRIIIa (42)either before or after DENV infection has been associated with increased dengue severity (43)(44)(45). Finally, the presence of serum complementsuch as C1q and C3 -can inhibit IgG mediated ADE both in vitro and in vivo, ostensibly by interfering with the ability of IgG Fc to interact with FcgR and/or forcing a complement-bound antibody into a configuration that is not amenable to fusion and viral entry (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…The well-known dengue ADE has been associated with poorly neutralizing cross-reactive antibodies against a heterologous viral serotype, leading to increased infection of FcγR-expressing cells 58 . Recent findings suggested that an increase in afucosylated antibodies contribute to dengue ADE 59 . In contrast, vaccine-associated enhanced respiratory disease induced by respiratory syncytial virus has not been found to be antibody-dependent 60 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, afucosylation of the HIV broadly neutralizing monoclonal antibody b12 did not enhance pre-exposure protection against a mucosal challenge in a rhesus macaque model, despite in vitro enhancement of ADCC activity, 95 yet postexposure therapeutic efficacy against an intraperitoneal challenge was enhanced via increased ADCC/ADCP accompanied by lower viral loads for a highly potent broadly neutralizing HIV antibody, 3BNC117, in a humanized mouse model. 94 Importantly, given recent associations between afucosylated antibodies and disease severity in the context of Dengue virus and SARS-CoV-2, 70,[96][97][98] reducing interaction with FcγR3A may be critical to avoid monoclonal antibody-mediated immunopathology for some viral infections.…”
Section: Lesson 1: Enhancing Effector Function Through the Fc Can Increase Therapeutic Antibody Potency And Efficacymentioning
confidence: 99%